Improving productivity of dragline through enhancement of reliability, inherent availability and maintainability - Mohammadi M.; Rai P.; Gupta S. (My University, 2025)
Achieving the high production and productivity target is one of the biggest challenges for any mineral industry, in order to remain competitive in the global market. The maximum production of mining equipment is possible by ensuring maximum reliability and maintainability, which results in increasing the availability of equipment. The present paper is an endeavor to compute inherent availability of dragline machine and critically analyze reliability and maintainability of dragline’s subsystems in one of the major open cast coal mines in India. The inherent availability of the studied dragline was 0.8402 (low). The Reliability, Availablity, and Maintainability (RAM) study has further highlighted the fact that the structural part with the maximum Mean Time To Repair (MTTR=88 h) and bucket subsystem with the minimum Mean Time To Failure (MTTF=54 h) are the major contributors to low inherent availability. © 2016, Technical University of Kosice. All rights reserved.